Variation in methane uptake by grassland soils in the context of climate change – A review of effects and mechanisms - Rafalska, Adrianna; Walkiewicz, Anna; Osborne, Bruce; Klumpp, Katja; Bieganowski, Andrzej (The Science of the total environment, 2023)
Grassland soils are climate-dependent ecosystems that have a significant greenhouse gas mitigating function through their ability to store large amounts of carbon (C). However, what is often not recognized is that they can also exhibit a high methane (CH4) uptake capacity that could be influenced by future increases in atmospheric carbon dioxide (CO2) concentration and variations in temperature and water availability. While there is a wealth of information on C sequestration in grasslands there is less consensus on how climate change impacts on CH4 uptake or the underlying mechanisms involved. To address this, we assessed existing knowledge on the impact of climate change components on CH4 uptake by grassland soils. Increases in precipitation associated with soils with a high background soil moisture content generally resulted in a reduction in CH4 uptake or even net emissions, while the effect was opposite in soils with a relatively low background moisture content. Initially wet grasslands subject to the combined effects of warming and water deficits may absorb more CH4, mainly due to increased gas diffusivity. However, in the longer-term heat and drought stress may reduce the activity of methanotrophs when the mean soil moisture content is below the optimum for their survival. Enhanced plant productivity and growth under elevated CO2, increased soil moisture and changed nutrient concentrations, can differentially affect methanotrophic activity, which is often reduced by increasing N deposition. Our estimations showed that CH4 uptake in grassland soils can change from −57.7 % to +6.1 % by increased precipitation, from −37.3 % to +85.3 % by elevated temperatures, from +0.87 % to +92.4 % by decreased precipitation, and from −66.7 % to +27.3 % by elevated CO2. In conclusion, the analysis suggests that grasslands under the influence of warming and drought may absorb even more CH4, mainly because of reduced soil water contents and increased gas diffusivity. [Display omitted] •In most cases, grasslands will remain CH4 sinks under future climatic scenarios.•Grassland soils subjected to warming and drought may absorb even more CH4.•Elevated CO2 effects on CH4 uptake in grasslands soils may be negligible.•Mean soil moisture may determine effect of climate change on methanotrophy.•It is important to recognize the effects of multiple interacting factors.